Testing a conceptual model on early opening of the microcirculation in severe sepsis and septic shock. Issue 3 (March 2015) - van der Voort, Peter H.J.; van Zanten, Mark; Bosman, Rob J.; van Stijn, Ilse; Wester, Jos P.J.; van Raalte, Rutger; Oudemans-van Straaten, Heleen M.; Zandstra, Durk F.
<x xml:space="preserve">Abstract</x> BACKGROUND Organ failure in severe sepsis and septic shock may be caused by microcirculatory failure. OBJECTIVE The objective of this study is to test a conceptual model of microcirculatory failure by using a resuscitation strategy targeting early opening of the constricted microcirculation with active vasodilatation. DESIGN A randomised controlled pilot study. SETTING Single-centre mixed medical and surgical tertiary ICU. PATIENTS Ninety severe sepsis and septic shock patients randomised to early opening microcirculation resuscitation group or standard resuscitation group. INTERVENTIONS Standard resuscitation group: fluids, noradrenaline, dobutamine and hydrocortisone were given to achieve a mean arterial pressure (MAP) of more than 60 mmHg, cardiac index more than 2.5 l min−1 m−2 and ScvO2 more than 70%. Microcirculation resuscitation group: nitroglycerin, enoximone, dopamine and dexamethasone targeting a microvascular flow index (MFI), measured by sublingual side-stream dark field imaging, more than 2.5. MAIN OUTCOME MEASURE A decrease in organ failure score (SOFA) on day four of ICU treatment. RESULTS Data from 37 microcirculation resuscitation and 28 standard resuscitation patients were analysed. In the microcirculation resuscitation group, MFI of more than 2.5 was achieved after a mean ± SD of 7.0 ± 4.6 h. The microcirculation resuscitation group received more fluids, and noradrenaline was equally prescribed in both groups. Per protocol, the decrease in SOFA score at day 4 was not different between groups (P = 0.64). There was a significant reduction in SOFA score in both groups compared with admission (1.2 and 1.6 in microcirculation resuscitation and standard resuscitation groups, respectively; P = 0.028 and P = 0.045). CONCLUSION Early opening of the microcirculation in patients with severe sepsis and septic shock using nitroglycerin, enoximone, dopamine and corticosteroids did not result in a faster reduction in organ failure than standard resuscitation. TRIAL REGISTRATION Clinicaltrials.gov identifier NCT00484133.